Image analysis and processing - ICIAP 2019 : 20th International Conference, Trento, Italy, September 9-13, 2019, proceedings.: 20th International Conference, Trento, Italy, September 9-13, 2019, proceedings. Part 2 ([2019]) - Unknown
No abstract available